Local Wisdom of Forest Business Community in Mallawa District, Maros Regency - Ayub, Muhamad Gafar; Dassir, Muh.; Ridwan, Muh. (Budapest International Research and Critics University, 2021)
The use of candlenut forest by the community has local wisdom that plays a role in the cultivation of forest candlenut by the community. This study aims to determine the role of local wisdom in the utilization of candlenut forest in Mallawa district. This research was conducted through direct observation and interviews with forest use actors regarding the types of timber harvested, timber sales transactions with harvest patterns, the wage system, the income of community forest workers and social institutions in community forest management. Data analysis was carried out quantitatively through income calculation and descriptive analysis to describe the role of local wisdom in the use of candlenut forest. The results showed that the community forest harvesting pattern, in which contractors buy wood at the price of tree stands to farmers who own community forest land, provides the highest income without cost to community forest owners. Local wisdom is manifested in various patterns of harvesting community forests, including: (1) the first harvest pattern: farmers who own community forests are assisted to rejuvenate the forest area, (2) the second harvest pattern: farmers can earn a lot of money quickly for urgent needs. needs, (3) the third harvest pattern, which provides easier access for local entrepreneurs to harvest and market community forest products, (4) and the fourth harvest pattern, farmers have the option to sell trees/timber on a small scale (multiple trees). If necessary, small funds. Local wisdom contained in the people's candlenut harvest includes (1) makkampiri activities, namely during the main harvest for candlenut forest owners to collect candlenut fruit and play a role in minimizing candlenut theft to be played, (2)